Cathepsin‐B Induced Controlled Release from Peptide‐Capped Mesoporous Silica Nanoparticles. Issue 47 (10th October 2014) - de la Torre, Cristina; Mondragón, Laura; Coll, Carmen; Sancenón, Félix; Marcos, María D.; Martínez‐Máñez, Ramón; Amorós, Pedro; Pérez‐Payá, Enrique; Orzáez, Mar
Abstract New capped silica mesoporous nanoparticles for intracellular controlled cargo release within cathepsin B expressing cells are described. Nanometric mesoporous MCM‐41 supports loaded with safranin O (S1‐P) or doxorubicin (S2‐P) containing a molecular gate based on a cathepsin B target peptidic sequence were synthesized. Solids were designed to show "zero delivery" and to display cargo release in the presence of cathepsin B enzyme, which selectively hydrolyzed in vitro the capping peptide sequence. Controlled delivery in HeLa, MEFs WT, and MEFs lacking cathepsin B cell lines were also tested. Release of safranin O and doxorubicin in these cells took place when cathepsin B was active or present. Cells treated with S2‐P showed a fall in cell viability due to nanoparticles internalization, cathepsin B hydrolysis of the capping peptide, and cytotoxic agent delivery, proving the possible use of these nanodevices as new therapeutic tools for cancer treatment.